The Study of Treatment of UTIS using Nanomaterials and Nanotechnology (Journal of Advances and Scholarly Researches in Allied Education, 2024)
If you have an infection in any of the four parts of your urinary system the kidneys, ureters, bladder, or urethra you have a urinary tract infection. The bladder and urethra, which are part of the lower urinary system, are the most common sites of infection. In comparison to males, women have a higher chance of getting a UTI. A bladder infection may be both uncomfortable and inconvenient. This study delves into several nanoparticles (NPs) used for the treatment of urinary tract infections (UTIs), including organic NPs, chemical NPs, and inorganic NPs that are green synthesized.